Synthesis of poly(N-acryloylmorpholine) macromonomers using RAFT and their copolymerization with methacrylic acid for the design of graft copolymer additives for concrete. Issue 4 (11th December 2015) - Boursier, T.; Georges, S.; Mosquet, M.; Rinaldi, D.; D'Agosto, F.
Abstract : Methacrylate end-capped poly( N -acryloylmorpholine) macromonomers (PNAM-MA) of number-average molar mass of about 2400 g mol −1 have been synthesized by post-modification of PNAM chains obtained by RAFT. Abstract : Methacrylate end-capped poly( N -acryloylmorpholine) macromonomers (PNAM-MA) of number-average molar mass of about 2400 g mol −1 have been synthesized by post-modification of PNAM chains obtained by RAFT. The good control of the NAM polymerization in the presence of a 2-cyano-2-thiothiopropylsulfanyl propane (CTPP) RAFT agent allowed the synthesis of highly thiocarbonylthio end-functionalized chains (89%). Two sequences of reactions have then been carried out in order to introduce a methacrylate functionality: the reduction of the thiocarbonylthio function into a thiol function by hydrazine followed by the reaction with isocyanatoethyl methacrylate (IEMA) or the one-pot aminolysis/Michael addition onto acryloyloxyethyl methacrylate (AOEMA), resulting in 77% and 86.5% of methacrylate functionality, respectively. The resulting macromonomers were successfully copolymerized with methacrylic acid (MAA) at a MAA : PNAM macromonomer molar ratio of 3 : 1 to afford graft copolymers that exhibit all the features of superplasticizers for concrete. Their stability towards alkaline conditions and high ionic strength usually met in concrete pore solutions has been assessed. The ester linkage resulting from the aminolysis/Michael addition sequence led to highly hydrolyzable side chains, which are therefore not appropriate for this application. The thiourethane linkage coming from the thiol–isocyanate chemistry, resisted the alkaline conditions of the interstitial concrete media and could potentially be used for novel concrete formulations.